Digital Transformation and Islamic Banks’ Financial Stability: The Role of Sustainable Economic Growth in Indonesia - Amila Zamzabila Putri; M. Yusril Hafidz Nur Izza (EkBis: Jurnal Ekonomi dan Bisnis, 2025)
This study aims to examine the relationship between digital transformation and the financial stability of Islamic banking in Indonesia, while analyzing the role of sustainable economic growth in moderating this relationship. Using static panel data regression with a sample of five Islamic banks in Indonesia from 2020 to 2024, the study measures bank stability through the Z-score indicator. The findings indicate that digital transformation, specifically through the number of ATMs and mobile banking usage (MU), has a significant impact on Islamic banking stability by enhancing operational efficiency and reducing transaction costs. Furthermore, Gross Domestic Product (GDP) serves as a significant interaction variable that strengthens the resilience of the Islamic banking system when combined with digital infrastructure like ATMs and commercial branches. The implications suggest that Islamic banks should leverage digital transformation to strengthen credit scoring systems and mitigate risks to ensure stability amidst macroeconomic dynamics. This study contributes to the literature by incorporating non-cash electronic financial service variables and evaluating the interaction effect of GDP on digitalization’s effectiveness within the Indonesian Sharia banking sector.